Wave Spectrum Change in The Vicinity of Artificial Reef - Armono, Haryo D; Kurniawan, Andi; Akhwady, Rudhy; _, Sujantoko (Journal of Indonesian Coral Reefs, 2011)
Artificial reefs have capability to enhance the environment, improve aesthetics and provide protection needed in certain coastal areas. The perforated hollow cylindrical shape artificial reefs are proposed as submerged breakwater due to characteristics that are not found in conventional breakwaters such as the water circulation and fish habitat enhancement capability. As submerged breakwater, the performance of artificial reefs are displayed by their capabilities in reducing wave energy. The change of wave energy spectrum in the vicinity of perforated hollow cylindrical shape artificial reefs is presented in this paper. The influence of wave steepness, relative reef height and relative reef width to the spectrum wave transmission were studied by physical model. The change of the wave spectrum were observed by comparing the area of the incoming wave spectrum to the transmitted wave spectrum. It is shown that the energy of incoming wave were reduced significantly by artificial reefs, providing the quiescent area in the shoreline.